Behind closed doors - Rose, Shain (Kept in Paradise, 2026)
He's the forbidden enigma I wanted to ignore . . . but instead I'll be forced to share a home with him. Jameson Knight arrives at precisely the same time every day to pick up his young daughter from school, smiling as she runs into his open arms. It's the only time I see him smile. I don't ask questions because it's not my place. I'm just his daughter's favorite teacher, nothing more. . . . Until the first bullet flies by us at recess. Suddenly, I'm risking my life to protect her. And then Jameson drags me back to his estate, claiming it's a matter of life-or-death. Now I'm in the most beautiful home I've ever seen, faced with an offer from a man who's just as gorgeous: Be the temporary live-in nanny until he can ensure my safety and find a more permanent solution. It'll be easy, he promises. Yet, the arrangement is anything but simple. Not when Jameson's hungry stare is all consuming and his touch pulse racing. And definitely not when I find that nothing in this neighborhood is as it seems, including Jameson. He may be powerful, possessive, and protective. But he's also dangerous, demanding, and calculating. As more of his secrets come out, I should run but ... How do I escape the enigma of Jameson Knight if he's already captured my heart?